2023
DOI: 10.3390/nano13040749
|View full text |Cite|
|
Sign up to set email alerts
|

Mesoporous Cobalt Oxide (CoOx) Nanowires with Different Aspect Ratios for High Performance Hybrid Supercapacitors

Abstract: Cobalt oxide (CoOx) nanowires have been broadly explored as advanced pseudocapacitive materials owing to their impressive theoretical gravimetric capacity. However, the traditional method of compositing with conductive nanoparticles to improve their poor conductivity will unpredictably lead to a decrease in actual capacity. The amelioration of the aspect ratio of the CoOx nanowires may affect the pathway of electron conduction and ion diffusion, thereby improving the electrochemical performances. Here, CoOx na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…There was an error in the original publication [ 1 ]. As the JCPDS Card 48-0083 is modified by new synchrotron X-ray powder diffraction data, the chemical composition and crystal structure of the CoO x -130 precursor require modification in the published article.…”
Section: Text Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was an error in the original publication [ 1 ]. As the JCPDS Card 48-0083 is modified by new synchrotron X-ray powder diffraction data, the chemical composition and crystal structure of the CoO x -130 precursor require modification in the published article.…”
Section: Text Correctionmentioning
confidence: 99%
“…In the original publication [ 1 ], Bhojane, P.; Bail, A.; Shirage P. A quarter of a century after its synthesis and with >200 papers based on its use, Co(CO 3 )0.5 30 (OH)·0.11H 2 O proves to be Co 6 (CO 3 ) 2 (OH) 8 ·H 2 O from synchrotron powder diffraction data. Acta Crystallogr.…”
Section: Citation Correctionmentioning
confidence: 99%
“…2D materials such as graphene and MXene with negative or relatively low coefficients of thermal expansion (CTE) (−3.26 × 10 −6 and 2.26 to 17.83 ×10 −6 K −1 , respectively) [235][236][237] can be combined with organic polymers, such as polytetrafluoroethylene (PTFE) and PDMS, with the CTE values of 3.56 × 10 −4 and 3 × 10 −4 K −1 , respectively, to trigger a programmable thermal actuation behavior. [212,238] While a heat is applied, the thermal coefficient mismatch leads to the desired actuation. [239] Hu et al reported reversible photothermal TRAs based on a bimorph structure of rGO/CNT and PDMS layer, demonstrating a large deformation angle of 479°under only 3.6 s sunlight irradiation.…”
Section: Thermo-responsive Actuatormentioning
confidence: 99%
“…[195] A bilayer actuator composed of PNIPAM hybridized with GO layer and hydroxyethyl methacrylate layer for photothermal effect and improved water transport, respectively, demonstrated reversible bending behavior upon thermal cycling. [238] Wang et al endowed the elastin-like polypeptide hydrogel actuators with grapheneenabled light-controllability, whose mechanical motions were readily tunable by the light intensity and irradiation direction (Figure 8c). [199] Thermotropic liquid crystalline elastomers (LCEs) are another platform for thermo-responsive soft actuation exhibiting a sizeable stimuli response.…”
Section: Thermo-responsive Actuatormentioning
confidence: 99%
“…Such methods offer the advantages of simplicity, affordability, speed and good control of particle size and morphology. The enhanced performance characteristics of nanomaterials prepared by wet chemical methods afford significant advantages for supercapacitor applications [ 22 , 23 , 24 , 25 ]. However, particles prepared by wet chemical methods are prone to agglomeration and particle growth due to Ostwald ripening.…”
Section: Introductionmentioning
confidence: 99%